PERANCANGAN APLIKASI PENGOLAHAN DATA PETANI IKAN BERDASARKAN STRATIFIKASI PENDIDIKAN DALAM MEMBUAT STRATEGI KEBIJAKAN PENGEMBANGAN USAHA - DYAH RHETNO WARDHANI (LPPM, 2015)
Cirata reservoir has the characteristics of public aquatic ecosystem that has a variety of potential socio-economic field. One of the potential benefits of Cirata is fish farming in a floating cage. Cirata only planned to hold no more than 12,000 floating cages. It’s number that has go beyond the carrying capacity of the reservoir boundary effect on the explosion of the amount of liquid waste discharged into waters entered. This leads to a decrease in fish production due to the reduced volume of stocked fish and make fish prices soar. The environment becomes one of the critical success factors. Another factor in helping the development of the business is qualified Human Resources. With the good quality of human resources, the environmental barriers can be minimized. To provide a good HR needs an adequate level of education. Research conducted to provide data and information that helps in making policy strategy in the development of fisheries based on educational stratification. The data processing by SEM PLS and SWOT analysis. From the data obtained it is made in the design of applications and databases that provide information such as determining factors in fisheries development policy making. Application will be made using the Java programming language that is connected to the database. Keywords: policy strategy, SEM PLS, SWOT analysis, Java